2015
DOI: 10.1371/journal.pone.0135645
|View full text |Cite
|
Sign up to set email alerts
|

Drug Authorization for Sofosbuvir/Ledipasvir (Harvoni) for Chronic HCV Infection in a Real-World Cohort: A New Barrier in the HCV Care Cascade

Abstract: BackgroundNew treatments for hepatitis C (HCV) infection hold great promise for cure, but numerous challenges to diagnosing, establishing care, and receiving therapy exist. There are limited data on insurance authorization for these medications.Materials and MethodsWe performed a retrospective chart review of patients receiving sofosbuvir/ledipasvir (SOF/LED) from October 11-December 31, 2014 to determine rates and timing of drug authorization. We also determined predictors of approval, and those factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 21 publications
(13 reference statements)
6
54
0
Order By: Relevance
“…These results echo some of the results from a study by Do et al,24 which found that one in four patients were initially denied access to sofosbuvir and ledipasvir, although most were eventually approved. The initial denial led to delays in the initiation of treatment, however.…”
Section: Barriers To Treatmentsupporting
confidence: 85%
See 2 more Smart Citations
“…These results echo some of the results from a study by Do et al,24 which found that one in four patients were initially denied access to sofosbuvir and ledipasvir, although most were eventually approved. The initial denial led to delays in the initiation of treatment, however.…”
Section: Barriers To Treatmentsupporting
confidence: 85%
“…Although DAAs have been shown to be, for the most part, cost-effective, they have not proven to be affordable 6. Data from the IFN era reveals that ∼16% of HCV-infected individuals were prescribed antiviral treatment, with only 9% achieving SVR 24. Given the significant number of undiagnosed patients with chronic HCV infection, this number is sobering and illustrates that cost is not the only barrier to DAAs.…”
Section: Barriers To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the progression rate increases with age [2], and given that the highest prevalence of HCV infection in the U.S. has been reported in the baby boomer population [3] who are currently between 50 and 70 years of age, the need for liver transplantation in HCV-infected patients is likely to remain high in the coming years. It is unclear whether the recently approved direct-acting antiviral (DAA) regimens for HCV, for which their high efficacy and minimal contraindications are at this point counter-balanced by access-related barriers [46], are able to reverse this trend at the national level any time soon.…”
Section: Introductionmentioning
confidence: 99%
“…DAA therapy usually requires prior authorization or preapproval from third-party payers due to high costs. Do et al8 found in a real-world HCV-infected cohort that 1 in 5 patients were denied access to these medications upon initial request. The majority of these initially denied patients eventually did receive prior authorization through the appeals process, with only 10% of patients unable to receive approval, indicating a potential administrative barrier that delays treatment of those who should be eligible 8…”
mentioning
confidence: 99%